Spermathecae of the mangrove crab Ucides cordatus: a histological and histochemical view - Sant'Anna, Bruno Sampaio; Pinheiro, Marcelo Antonio Amaro; Mataqueiro, Marcia; Zara, Fernando Jose (Cambridge University Press, 2007)
Ucides cordatus is the most commercially, important mangrove crab in Brazil. In spite of its economic importance, there are few studies of its reproduction, in particular the female reproductive system. The present study describes the histology and histochemistry of the spermathecae of U. cordatus. Adult females were can lit monthly from July 2004 through June 2005, at Iguape, State of São Paulo. The crabs were anaesthetized, and their spermathecae removed and fixed in Davidson's fluid, following the histological routine for paraffin. The slides were stained with HE, xylidine Ponceau, PAS, alcian blue (pH 1.0 and 2.5), Sudan black B and picrosirius-haematoxylin. Histologically, the spermathecae possesses a capsule of conjunctive tissue, rich in collalgen fibres, which surrounds the secretory columnar epithelium. In the lumen, individual sperm packets are not observed; the spermatophores are intermixed with the seminal fluid and secretions of the spermathecae itself. A large proportion of the free spermatozoids and spermatophores are arranged in homogeneous masses in the proximal part of the spermathecae. The secretion produced by the columnar epithelium appears to promote the movement of the gametes to the fertilization chamber, in a ventral position, allowing fertilization of the oocytes. Histochemically, the secretion produced by the columnar epithelium was strongly positive for neutral polysaccharides, positive for acid polysaccharides, and weakly positive for proteins and lipids. Tills secretion forms a glycoprotein matrix which is associated with maintenance of the spermatophores, which can remain stored for long periods.